Broadening the perspective of supply chain finance: The performance impacts of network power and cohesion. Issue 2 (March 2019) - Carnovale, Steven; Rogers, Dale S.; Yeniyurt, Sengun
Abstract: Because firms do not operate in isolation, they are bound by the structure of the networks in which they are embedded. This structure has implications on a firm's ability to access resources and utilize them to their advantage. We consider two critical components of this network structure: network power and network cohesion. Both of these network structures can be critical determinants of firm financial success. Yet, to date the extant research has not yet considered the role of network relations in the context of Supply Chain Finance (SCF). This manuscript attempts to contribute to this gap. Through the use of a dynamic supply chain network structure, we test the role that network power and cohesion have on a firm's financial performance. The results indicate network cohesion contributes positively to efficiency in financial performance, whereas power is a critical factor in earnings performance. Taken together, the study advances a nuanced perspective of managing the firm's levels of network power and cohesion to allow for heightened financial performance. Highlights: The effect of network structure on financial performance given resource dependencies is studied. Hypotheses examine the effect of network power and network cohesion on a firm's CCC, EBITDA and ROA. Results suggest network cohesion engenders efficiency in financial performance. Results also suggest network power engenders earnings performance. Managing the firm's levels of network power and cohesion facilitate improved financial performance.